Pengaruh Orientasi Pasar, Orientasi Kewirausahaan Dan Orientasi Strategik Terhadap Inovasi Produk Pada PDAM Tirta Mahakam Di Tenggarong - Catur Romadhasari; Erwinsyah Erwinsyah; Mawardi Mawardi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:               The purpose of this research is to find out whether the market orientation variable, entrepreneurial orientation and strategic orientation do simultaneous influence on product innovation in PDAM Tirta Mahakam in Tenggarong, to find out market orientation variables, entrepreneurial orientation and strategic orientation whether it has a positive effect on product innovation, and among these variables which variable has the most dominant influence on product innovation of PDAM Tirta Mahakam in Tenggarong.The data analysis tool used to determine the effect of the independent variables of market orientation, entrepreneurial orientation and strategic orientation with the dependent variable of innovation in drinking water products in tuah bumi packaging on PDAM Tirta Mahakam is multiple linear regression. A significant 5% technique means that there will be a two-sided test of the sample used. The t test will be used to compare whether the results of t count are greater or smaller than t table or vice versa.The results of the research F value calculated is 24,588 while F table is 0,275. This means that F count > F table means that it can be said that the market orientation, entrepreneurial orientation and strategic orientation variables are jointly able to show their influence on product innovation or regression models can be used to predict product innovation, so that the first hypothesis is accepted and proven to be true The results of the study Partial values in this study indicate that the orientation of the enterprise, entrepreneurial orientation and strategic orientation have a simultaneous influence, market orientation does not affect product innovation and entrepreneurial orientation has a positive effect on innovation and strategic orientation also positively influences product innovation. Furthermore, there is a variable that has the dominant influence on the product innovation of PDAM Tirta Mahakam is strategic orientation. Thus H1 is accepted H2 is rejected, it is not proven that H3 is accepted H4 is accepted and H5 is accepted and proven correctKeywords: Market Orientation, Entrepreneurship Orientation and Strategic Orientation and Product Innovation.